Seismic Response Characteristics of Stabilizing Pile Based on Elastic-Plastic Analysis - Honglue Qu; Ying Liu; Hao Luo; Huanguo Hu; Qindi Hu (Shock and Vibration)
Stabilizing pile is widely used in the landslide controlling projects and shows excellent seismic performance under the action of earthquake. Therefore, in order to improve seismic design theory, it is of importance to study the seismic response characteristics of stabilizing pile based on elastic-plastic analysis. In view of this, elastic-plastic constitutive model was established to deduce the plastic zone of stabilizing pile. Based on elastic-plastic analysis, the seismic response characteristics and the influence of different section sizes, material strengths, and peak ground motion acceleration (PGA) were analyzed by ANSYS 3D. Resultantly, the elastic-plastic fourth-order tensor Cijklep was deduced, which can be used to calculate plastic strain of stabilizing pile under loading. Compared with Chinese code, the material of stabilizing pile working with elastic-plastic state will be decreased under the same section size and the same property. Furthermore, stabilizing pile is in the elastic stage at the beginning under the action of earthquake. With the increase of ground motion time, the section starts to exhibit elastic-plastic state and then the plastic zone expands gradually. Finally, the plastic zone runs through the whole section, resulting in the performance loss of the pile. In addition, under the different design parameters, pile shows different seismic response characteristics; namely, changing these parameters reasonably can improve the seismic design.